Association of Chest Pain and Risk of Cardiovascular Disease with Coronary Atherosclerosis in Patients with Inflammatory Joint Diseases - Rollefstad, Silvia; Ikdahl, Eirik; Hisdal, Jonny; Kvien, Tore Kristian; Pedersen, Terje Rolf; Semb, Anne Grete (Frontiers in Medicine, 2015)
Objectives: The relation between chest pain and coronary atherosclerosis (CA) in patients with inflammatory joint diseases (IJD) has not been explored previously. Our aim was to evaluate the associations of the presence of chest pain and the predicted 10-year risk of cardiovascular disease (CVD) by use of several CVD risk algorithms, with multi-detector computer tomography (MDCT) coronary angiography verified CA. Methods: Detailed information concerning chest pain and CVD risk factors was obtained in 335 patients with rheumatoid arthritis (RA) and ankylosing spondylitis (AS). In addition, 119 of these patients underwent MDCT coronary angiography. Results: Thirty-one percent of the patients (104/335) reported chest pain. Only 6 patients (1.8%) had atypical angina pectoris (pricking pain at rest). In 69 patients without chest pain, two thirds had CA, while in those who reported chest pain (n=50), CA was present in 48.0%. In a logistic regression analysis, chest pain was not associated with CA (dependent variable) (p=0.43). About 30% (Nagelkerke R2) of CA was explained by any of the CVD risk calculators: SCORE, Framingham Risk Score or Reynolds Risk Score. Conclusion: The presence of chest pain was surprisingly infrequently reported in patients with IJD who were referred for a CVD risk evaluation. However, when present, chest pain was weakly associated with CA, in contrast to the predicted CVD risk by several risk calculators which was highly associated with the presence of CA. These findings suggest that clinicians treating patients with IJD should be alert of coronary atherosclerotic disease also in absence of chest pain symptoms.